Characteristics of urban boundary layer in heavy haze process based on Beijing 325m tower data. Issue 1 (2nd January 2019) - Yu, Shi; Fei, HU; Rui, LÜ; Yuanyuan, HE
ABSTRACT: Beijing experienced serious haze pollution from 24 November 2015 to 2 December 2015. To investigate the planetary boundary layer characteristics, especially turbulence characteristics, the authors analyzed the wind, temperature, humidity, and turbulence characteristics during heavily polluted weather by using the observational data of the 325-m meteorological tower in Beijing. The results indicate that the pollution was mainly caused by the easterly and southerly winds. There were negative correlations between wind speed, turbulent kinetic energy, friction velocity, and the PM2.5 concentration. During clean days, the wind speed greatly enhanced with height; however, during the period of heavy pollution, the wind speed changed a little from the near-surface layer to the top of the tower. In contrast, the spatial variability of TKE from the near-surface layer to the upper layer was not so obvious. The heavy haze pollution in this study was often characterized by the emergence of an inversion layer; therefore, the diurnal variation of the boundary layer temperature was very small. At the time of serious pollution, the relative humidity was near 100%. The diurnal variations of sensible heat flux and water vapor flux were significantly reduced when severe pollution occurred. Graphical Abstract: